MOLLUSCA AND ARTHROPODA ABUDANCE IN THE ECOSYSTEM AREA OF MANGROVE SUNGAITOHOR VILLAGE KEPULAUAN MERANTI REGENCY, RIAU PROVINCE - Said Nazman Arif; Joko Samiaji; Sofyan Husein Siregar (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT This research was conducted in November 2017 - April 2018 in the ecosystem area of mangrove Sungaitohor Village, Kepulauan Meranti Regency, Riau Province. The aim of the study was to determine the type and abundance of molluscs and arthropods, as well as the species diversity index (H'), uniformity index (E) and dominance index (C) of molluscs and arthropods. The method used was a survey method consisting of 3 stations with transect perpendicular to the coastline. The number of molluscs and arthropods at the study area was 10 species, consisting of 8 species the Molluscs and 2 other species from Arthropods phylum. The average abundance of molluscs and arthropods ranged from 2,11 x 104 – 4,00 x 104 ind/ha and the abundance of molluscs and arthropods between stations was significantly different (P < 0.01). The average Diversity Index (H') was 3.0628 indicating high diversity; the average Dominance Index (C) was 0.1333 indicating that no spesies dominates the site. The Diversity Index (E) was 0.9367 indicating the uniformity of organisms in a balanced state and there was no competition for places or foods. Keywords: abundance, molluscs and arthropods, mangrove ecosystem, meranti